2004
DOI: 10.1097/01.jcp.0000130558.86125.5b
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Risperidone-Induced Weight Gain Across the Age Span

Abstract: A systematic and comprehensive literature search was performed to determine the extent of weight gain induced by risperidone (RIS) treatment across the age span. The review and pooled data analyses were based on double-blind, open trial, and case series studies containing findings on drug dose, age of subjects, weight gain, duration of treatment, and if available, baseline body weight, body mass index, and the percent of subjects experiencing a prominent RIS-induced weight gain. Drug-induced weight gain per mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(68 citation statements)
references
References 66 publications
5
63
0
Order By: Relevance
“…Atypical antipsychotic monotherapy studies in children and adolescents suggest that this risk stratification may be similar (Stigler et al 2004), but weight gain may be characteristic of all atypical antipsychotics in previously antipsychoticnaive youths. Atypical antipsychotic-induced weight gain may be greater in the pediatric population compared to adults (Safer 2004). Along with the clinical consequences of type 2 diabetes mellitus, hypertension, and dyslipidemia (Boyd et al 2005;Must et al 1999), excessive weight gain in youths may result in problems with self-esteem, social functioning, and medication adherence (Patel et al 2005).…”
Section: Introduction Ementioning
confidence: 99%
“…Atypical antipsychotic monotherapy studies in children and adolescents suggest that this risk stratification may be similar (Stigler et al 2004), but weight gain may be characteristic of all atypical antipsychotics in previously antipsychoticnaive youths. Atypical antipsychotic-induced weight gain may be greater in the pediatric population compared to adults (Safer 2004). Along with the clinical consequences of type 2 diabetes mellitus, hypertension, and dyslipidemia (Boyd et al 2005;Must et al 1999), excessive weight gain in youths may result in problems with self-esteem, social functioning, and medication adherence (Patel et al 2005).…”
Section: Introduction Ementioning
confidence: 99%
“…65 Children are at particularly high risk of weight gain. 66 Mechanisms involved in weight gain and associated adverse metabolic changes probably include sedation and inactivity, perhaps more specific effects of central blockade of H 1 and 5-HT 2C receptors, as well as specific factors associated with the psychiatric disorder. 8,67,68 Hyperlipidemia and hyperglycemia with resultant type 2 diabetes mellitus have been associated with modern antipsychotic agents.…”
Section: Endocrine and Metabolic Effectsmentioning
confidence: 99%
“…It may apply to any type of psychotropic drug treatment and may refer also to medical adverse effects (e.g., metabolic syndrome after antipsychotic drugs) and potentially to any field of pediatric medicine. For example, evidence from a systematic review of literature showed that subjects aged from 5 to 17 years were more likely than adults to develop weight gain when treated with the second-generation neuroleptic risperidone [29]. Nonpsychiatric drugs may cause behavioral toxicity as well [30,31].…”
Section: Resultsmentioning
confidence: 99%